2021
DOI: 10.4102/phcfm.v13i1.2653
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a supportive-educative nursing intervention programme on knowledge of chlorhexidine gel for umbilical cord management amongst mothers in Cross River State, Nigeria

Abstract: The global prevalence of neonatal infection remains high and accounts for one-third of neonatal deaths (1.5 million), with umbilical cord infection as the major risk factor, especially in low-income countries. 1,2 Hospital-based studies in Nigeria revealed that umbilical cord infections account for about 10% -19% of neonatal admissions, resulting in 30% -49% of deaths in neonates. 3 Nigeria therefore ranks the second highest globally, with 276 000 deaths annually resulting from umbilical cord infection. 4,5 In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
(24 reference statements)
2
3
0
Order By: Relevance
“…Some believed hospitals were a good option while others felt the use of herbal remedies would take care of any cord-related infections. Concerning the management of cord infections, our findings are similar to those of Osuchukwu, et al [ 31 ] which showed that only a few caregivers visited the hospital when the cords were infected while the majority managed the infections at home with herbs. Muella and Johnson [ 34 ] found that only few mothers treated cord infections in the hospital as against the numerous others that preferred to manage their babies at home.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Some believed hospitals were a good option while others felt the use of herbal remedies would take care of any cord-related infections. Concerning the management of cord infections, our findings are similar to those of Osuchukwu, et al [ 31 ] which showed that only a few caregivers visited the hospital when the cords were infected while the majority managed the infections at home with herbs. Muella and Johnson [ 34 ] found that only few mothers treated cord infections in the hospital as against the numerous others that preferred to manage their babies at home.…”
Section: Discussionsupporting
confidence: 89%
“…Some participants mentioned death of children as one of the complications from improper care of baby's cord. The complications of improper cord care experienced by the participants of this study are similar to those reported among mothers in Calabar in Cross River State, Nigeria by Osuchukwu, et al in 2018 [31]. The women in that study reported symptoms such as fever, red skin around base of cord and foul smell due to cord infection.…”
Section: Discussionsupporting
confidence: 87%
“…12 In another study, poor knowledge of chlorhexidine gel for cord care in 62.8% of the mothers was found. 13 Similarly, in a study of forty health facilities, no newborn received the full package of essential newborn care. 14 In Ebonyi State, only 56.6% of women of reproductive age who had a live birth five years preceding the latest Demographic Health Survey delivered in a health facility; 58.3% had their deliveries attended by a skilled provider.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Evidence from Nigeria, suggests suboptimal to moderate levels of knowledge and practice of essential newborn care. 12 , 13 For example in one study, 59.3% practiced immediate skin to skin contact while only 10.1% initiated breastfeeding within 30 minutes of birth. 12 In another study, poor knowledge of chlorhexidine gel for cord care in 62.8% of the mothers was found.…”
Section: Introductionmentioning
confidence: 99%
“…It has been affirmed in previous research that a supportive educative nursing intervention programme could effectively improve the knowledge of CHX gel for umbilical cord management among mothers. 36 …”
Section: Discussionmentioning
confidence: 99%